Identification of susceptibility loci and genes for colorectal cancer risk - Zeng, Chenjie; Brenner, Hermann (Gastroenterology, 2016)
Background & Aims - Known genetic factors explain only a small fraction of genetic variation in colorectal cancer (CRC). We conducted a genome-wide association study to identify risk loci for CRC. - Methods - This discovery stage included 8027 cases and 22,577 controls of East-Asian ancestry. Promising variants were evaluated in studies including as many as 11,044 cases and 12,047 controls. Tumor-adjacent normal tissues from 188 patients were analyzed to evaluate correlations of risk variants with expression levels of nearby genes. Potential functionality of risk variants were evaluated using public genomic and epigenomic databases. - Results - We identified 4 loci associated with CRC risk; P values for the most significant variant in each locus ranged from 3.92 × 10−8 to 1.24 × 10−12: 6p21.1 (rs4711689), 8q23.3 (rs2450115, rs6469656), 10q24.3 (rs4919687), and 12p13.3 (rs11064437). We also identified 2 risk variants at loci previously associated with CRC: 10q25.2 (rs10506868) and 20q13.3 (rs6061231). These risk variants, conferring an approximate 10%-18% increase in risk per allele, are located either inside or near protein-coding genes that include transcription factor EB (lysosome biogenesis and autophagy), eukaryotic translation initiation factor 3, subunit H (initiation of translation), cytochrome P450, family 17, subfamily A, polypeptide 1 (steroidogenesis), splA/ryanodine receptor domain and SOCS box containing 2 (proteasome degradation), and ribosomal protein S2 (ribosome biogenesis). Gene expression analyses showed a significant association (P < .05) for rs4711689 with transcription factor EB, rs6469656 with eukaryotic translation initiation factor 3, subunit H, rs11064437 with splA/ryanodine receptor domain and SOCS box containing 2, and rs6061231 with ribosomal protein S2. - Conclusions - We identified susceptibility loci and genes associated with CRC risk, linking CRC predisposition to steroid hormone, protein synthesis and degradation, and autophagy pathways and providing added insight into the mechanism of CRC pathogenesis.
Gesehen am 04.09.2019